Contaminación coronaria post endodoncia como causa de fracaso endodóntico” - Mayra Elizabeth, Heredia Aisalla (2021)
ABSTRACT Post-endodontic coronary contamination as a cause of endodontic failure is a topic that has currently gained importance in endodontic practice. Contamination between endodontic completion and final restoration may alter the prognosis of the treatment. Therefore, coronal microleakage is considered the main factor in endodontic failure since microorganisms from the oral environment can enter the root canal and reach the apical portion in a matter of days, with greater probability when there is an absence of permanent restorations or through defective restorations, temporary restorations or through fractures. The method used was the collection of scientific articles from the databases Google Scholar, PubMed, Elsevier, Scielo through the criteria of exclusion, inclusion, filters, average citation count (ACC), journal impact factor that publishes the article through Scimago Journal Ranking (SJR), after all these tools were applied, a total of 89 articles were obtained for the systematic review. Once the selected articles were analyzed, it was established that the existence of post-endodontic contamination through the coronal portion is evident according to 69% of the studies analyzed. Therefore, the quality of the restoration is equally or even more important than the quality of the actual root canal treatment for the outcome of endodontic treatment. Keywords: Endodontics, coronal contamination, microleakage, post-endodontic restoration. Reviewed by: MsC. Edison Damian Escudero ENGLISH PROFESSOR C.C.0601890593